Shape-selective oriented cerium oxide nanocrystals permit assessment of the effect of the exposed facets on catalytic activity and oxygen storage capacity - Sreeremya, Thadathil S.; Krishnan, Asha; Remani, Kottayilpadi C.; Patil, Kashinath R.; Brougham, Dermot F.; Ghosh, Swapankumar (ACS Applied Materials & Interfaces, 2015)
The catalytic performance of a range of nanocrystalline CeO2 samples, prepared to have different morphologies, was measured using two accepted indicators; oxygen storage and diesel soot combustion. The same powders were characterized hi detail by HR-TEM, XRD, XPS, and Raman methods. The study demonstrates that activity is determined by the relative fraction of the active crystallographic planes, not by the specific surface area of the powders. The physical study is a step toward quantitative evaluation of the relative contribution to activity of the different facets. The synthetic protocol permits fabrication of CeO2 nanostructures with preferentially grown active planes, and therefore has potential in developing catalytic applications and in nanocompositing.
Keywords: ceria; chemical activities; crystal facets; nanocrystals; texture coefficient

Activity tuning of cobalt ferrite nanoparticles anchored on N-doped reduced graphene oxide as a potential oxygen reduction electrocatalyst by Zn substitution in the spinel matrix - Kashyap, Varchaswal; Singh, Santosh K.; Kurungot, Sreekumar (Chemistry Select, 2017)
Development of highly efficient and durable ORR catalysts by using non-platinum group metals (such as Co, Fe, Mn, and Zn) is a challenging task in the forward path towards the realization of low-cost energy devices in the commercial stream. The present work deals with an effective strategy wherein an efficient Pt-free electrocatalyst for oxygen reduction reaction (ORR) is prepared by stoichiometrically substituting some fraction of Fe with Zn in cobalt ferrite and anchoring these spinel nanoparticles on nitrogen doped reduced graphene oxide (N-rGO). Zn substitution is found to be significantly altering the ratio of Fe2+/Fe3+ in the cobalt ferrite nanocrystal system with a concomitant promotional influence on its electrocatalytic activity towards ORR. The nanoparticle composition with a Co, Fe and Zn molar ratio of 1.0:1.7:0.3, represented by the formula CoFe1.7Zn0.3O4(CFZn(0.3)), supported over N-rGO has shown 10 mV and 20 mV positive shift in the onset and half-wave potentials, respectively, for ORR in 0.1 M KOH in comparison to the nanoparticles of CoFe2O4 supported over N-rGO (CF/N-rGO). The optimum Zn substitution is found to be narrowing down the difference with the state-of-the-art Pt/C for ORR by 100 and 110 mV in terms of the onset and half-wave potentials, respectively. Most significantly, the homemade catalyst is found to be clearly outperforming the Pt catalyst in terms of the limiting current density and electrochemical durability.
Keywords: Carbon Nano-fiber; Cathod Catalyst; CoFe2O4; Evolution; Magnetic-properties; Membrane fuel- Cell; Metal-Air Batteries; N-doped graphene; Nanocrystalline; nanocrystals; oxygen reduction reaction; performance; Platinium; solvothermal synthesis; Zn substituted cobalt ferrite

Size-controlled cobalt ferrite nanocrystals: magnetically separable reusable nanocatalysts for selective oxidation of styrene - Jeyavani, Vijayakrishnan; Pawar, Sayali; Dadwal, Arun; Joy, Pattayil Alias; Mukherjee, Shatabdi Porel (ChemistrySelect, 2019)
Superparamagnetic cobalt ferrite (CFO) nanocrystals (NCs) with sizes similar to 6 nm and similar to 4 nm were synthesized using a facile solvothermal method using fatty acids, lauric acid and stearic acid, as the capping agents. The synthesized nanocrystals were well characterized by XRD, FT-IR, XPS, SEM and TEM. The formation mechanism was explored and it was shown that the fatty acid was actually chemisorbed as a carboxylate onto the surface of CFO NCs. The experimental results specify that the size and size distribution of the CFO NCs were highly dependent on the length of fatty acid hydrophobic chain. Corresponding changes of the magnetic properties were investigated by measuring magnetization as a function of field and temperature, which suggest that the CFO NCs were superparamagnetic in nature. The catalytic properties for the oxidation of styrene in organic medium were examined by using the synthesized CFO NCs with sizes similar to 6 nm and similar to 4 nm. The synthesized CFO NCs, well dispersible in organic media, were demonstrated to be highly catalytically active, reached 100% conversion of styrene in 12 h with similar to 77% and similar to 82% selectivity for styrene oxide respectively. The magnetic CFO nanocatalysts were easily separated and recovered from the reaction medium by an external magnet, and reused for several cycles without losing catalytic selectivity for styrene oxide.
Keywords: Cobalt ferrite; epoxidation; Fatty acids; magnetic properties; nanocrystals